DEVELOPMENT OF PARTICIPATIVE LEARNING MODELS TO IMPROVE ACHIEVEMENT OF EDUCATORS’ FOR VILLAGE MIDWIVES IN BANGKALAN - Rodiyatun .; Sutio Rahardjo; Moh Choirin (Poltekkes Kemenkes Surabaya, 2016)
Midwife is one of health professionals who has an important and strategic position in systemof health service. In conducting her profession, midwife has a role and function clearly regulated onstandard of midwifery care including a role as caregiver, manager, educator, and, researcher. Inrelation to her role as an educator, midwife has a responsibility in guiding healthy behavior andpromotion of health program in mothers, children, family planning and reproduction health.Improvement of midwives’ skills at performing his role as an educator can be conductedthrough participative learning strategy which involves midwives actively in informal learningprocess. Participative Learning Model is learning activity conducted from knowledge, values andskills owned by learners and emphasizing on problem solving approach.The aim of research was to develop participative learning model to improve achievement ofmidwife’s role as an educator. This research employed experiment, pretest-posttest control groupdesign, consisting of two groups, experiment group and control group. Independent variable wasparticipative learning model and dependent variable was midwife’s role as an educator. Dataanalysis technique used descriptive analysis and it was assumed that this research was conductedon population. Analysis of effects of participative learning model on achievement of midwife’s roleas an educator was based on median and mode values of pretest and posttest using Wilcoxon test.The result showed that there was a percentage increase of achievement in educator’s rolewhich was categorized tolerant in all competence of educator’s role. Wilcoxon test showed that pvalue,(0,046) α (0,05) means that development of participative learning model with observationand reflection had effects on increase of achievement in midwife’s role as an educator for healthservice in mothers, children and family planning (KB)/reproduction health.Guidance efforts of improving technical quality and knowledge development of villagemidwives needs to be conducted continuously through informal education held based on properneed analysis which is suitable with social cultural characteristics of society within their duty area.